Particle deposition onto charge heterogeneous surfaces convection-diffusion-migration model - Nazemifard, Neda (Langmuir : the ACS journal of surfaces and colloids, 2006)
The role of surface charge heterogeneity of planar collectors on particle deposition and distribution was investigated in the vicinity of a heterogeneous surface for a radial impinging jet flow geometry. The charge heterogeneity was modeled as concentric circular stripes bearing different surface charges. Particle deposition was studied employing the Eulerian approach (convection-diffusion-migration equation). It was observed that when the collector was completely unfavorable, the presence of small amounts of charge heterogeneity in the form of a small fraction of favorably charged stripes enhanced the deposition rate substantially. In contrast, when the collector was completely favorable, the presence of small amounts of charge heterogeneity in the form of a small fraction of unfavorably charged stripes did not affect the particle deposition rate significantly